The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1158/1078-0432.ccr-13-2567
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Germline Polymorphism Predictors of Prostate Cancer Progression in the Estradiol Pathway

Abstract: Purpose: Reliable biomarkers that predict prostate cancer outcomes are urgently needed to improve and personalize treatment approaches. With this goal in mind, we individually and collectively appraised common genetic polymorphisms related to estradiol metabolic pathways to find prostate cancer prognostic markers.Methods: The genetic profiles of 526 men with organ-confined prostate cancer were examined to find common genetic polymorphisms related to estradiol metabolic pathways and these findings were replicat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…These conflicting results indicate that the role of SULT2B1b in different cancers is varies with the type of cancer. Recently, several single-nucleotide polymorphisms (SNP) in SULT2B1 gene have been reported to be associated with risk of progression in prostate and esophageal carcinomas [28,29]. Additionally, earlier studies demonstrated that expression of SULT2B1b was significantly increased in breast and liver cancer tissues relative to their corresponding non-tumor counterparts [7,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting results indicate that the role of SULT2B1b in different cancers is varies with the type of cancer. Recently, several single-nucleotide polymorphisms (SNP) in SULT2B1 gene have been reported to be associated with risk of progression in prostate and esophageal carcinomas [28,29]. Additionally, earlier studies demonstrated that expression of SULT2B1b was significantly increased in breast and liver cancer tissues relative to their corresponding non-tumor counterparts [7,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the 1245C variant also appears to be a predictor of sensitivity to the steroidal CYP17 inhibitor abiraterone . Genomic variation in estrogen-related genes has also been reported in PCa patients (Lévesque et al 2014). This includes somatic polymorphisms in CYP1B1, HSD17B2, SULT2B1 and COMT genes.…”
Section: Genomic Alterations Implicating Sex Steroids In Prostate Canmentioning
confidence: 95%
“…This includes somatic polymorphisms in CYP1B1, HSD17B2, SULT2B1 and COMT genes. Further, the cumulative number of alterations appears to correlate with poorer outcome (Lévesque et al 2014). Similarly, SNPs in the CYP19A1 aromatase are associated with concomitant changes in serum estrogen levels and poorer PCa survival, but have no effect on PCa incidence (Travis et al 2009, Kanda et al 2015.…”
Section: Genomic Alterations Implicating Sex Steroids In Prostate Canmentioning
confidence: 99%
“…Germline variations in genes involved in the biosynthesis and metabolism of androgens and estrogens have been associated with progression of PCa , Levesque et al 2013, 2014a. The relevance of studying steroidogenic pathways in the context of progression of PCa arises from observations that PCa tumor cells can use multiple biotransforming pathways to de novo synthesize more potent hormones (Montgomery et al 2008, Mitsiades et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In support of these results, we have recently reported that singlenucleotide polymorphisms (SNPs) in genes associated with E 2 -related metabolic pathways, either individually or in combination, are predictors of progression of PCa. These variants are located in genes encoding cytochrome P450 1B1, which is involved in the production of 4-hydroxy metabolites of E 2 and E 1 (4-OH), catechol-O-methyltransferase, which forms 2-methoxy catechol estrogens, sulfotransferase 2B1, which catalyzes the formation of less-reactive sulfate metabolites, and 17b-hydroxysteroid dehydrogenase type 2, which is involved in the conversion of E 2 to E 1 (Levesque et al 2014a). However, it remains unclear whether the outcome of PCa is influenced by common germline polymorphisms in the estrogen catabolic pathway mediated by UGT1 gene products.…”
Section: Introductionmentioning
confidence: 99%